Effectiveness of Environmentally Friendly Mosquito Trap Contained Sugar Yeast Solution (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Environmentally friendly mosquitoes trap using common daily materials used by community may give hopes in reducing mosquitoes density. This study aims to determine the effectiveness of environmentally friendly mosquitoes trap made from bottle contained sugar yeast solution for reducing the number of trapped mosquitoes. This study consist of two phases and quasi experimental design was used. Mann Whitney test was used to determine the differences the number of trapped mosquitoes indoor and outdoor. The result showed p value 0,000 which was lower than α value (0,05), so there was significant difference between the number of indoor and outdoor trapped mosquitoes. The average Rank score of outdoor mosquitoes trap (42,75) was more than indoor mosquitoes trap (18,25). We concluded that the mosquitoes trapped which contained of sugar-yeast solution was effective for trapping the mosquitoes especially outdoor .